Эффекты переключения и памяти в МОП-структурах Al–SiO2–Si - Iskender-zade, Z. A.; Akhundov, M. R.; Jafarova, E. A.; Alikhanova, Sh. A. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
By studying current-voltage characteristics and non-stationary transient processes, the mechanisms of switching and memory effects in Al–SiO2–Si structures have been clarified, as well as the possibility of their practical application in the creation of stable and controllable memory elements.